Peningkatan Literasi Fisika melalui Pembelajaran Kontekstual Berbantuan Kecerdasan Buatan: Sebuah Inovasi dalam Pendidikan Fisika - Lili Istiqomah (International Journal of Contextual Science Education, 2026)
In the digital transformation era, the integration of Artificial Intelligence (AI) in education provides new opportunities to enhance students’ understanding and engagement in physics learning. This study aims to examine how AI-augmented contextual learning can enhance physics literacy among secondary school students. Physics literacy refers to students’ ability to understand, interpret, and apply physics concepts in solving real-world problems, supported by critical and analytical thinking skills. The AI-augmented contextual learning approach combines contextualized learning experiences—where physics concepts are related to everyday life situations—with AI-based tools such as virtual simulations, intelligent feedback systems, and adaptive learning platforms. This mixed-method study involves both quantitative and qualitative analyses to evaluate improvements in students’ literacy levels, conceptual understanding, and learning motivation. The expected results indicate that the integration of AI within contextual learning environments fosters deeper conceptual comprehension, strengthens problem-solving abilities, and encourages students to view physics as relevant and meaningful in daily life. Therefore, this research contributes to promoting innovative, future-oriented physics education by leveraging AI technology to cultivate scientifically literate and future-ready learners.